Pengaruh Model Discovery Learning Berbantuan Media Audio Visual dalam Setting Lesson Study Terhadap Hasil Belajar IPA Mahasiswa PGSD Undiksha UPP Denpasar Tahun 2017 - Komang Putri Lestari (Jurnal Ilmiah Sekolah Dasar, 2018)
This research is intended to know the influence of NHT model by audio visual media toward the mastery of science competence of fourth grade students of SD Gugus Yos Sudarso in academic year 2016/2017. Type of research conducted in this research is quantitative research with experimental design that is quasi experiment (Experimental Semu). The experimental design used is "Nonequivalent control group design". In the two samples that have been drawn are one group of expreiments and one control group. Class IVB SDN 12 Sanur as experimental group and grade IVC SDN 10 Sanur as control group. The learning in the experimental and control class is equally given 6 times, and is given the last postet to know the improvement of the knowledge competence of science knowledge. To collect data in this research is done by test method. The data obtained were analyzed using the t-test. The results of data analysis obtained thitnung = 6,536 while at the level of significance 5% and dk = 68 obtained t table = 2,000 so thitung = 6,536 > t table = 2,000. Based on the test criteria, Ho is rejected and Ha accepted. The average value of science knowledge competence in the group that was taught with NHT model with audio visual aid wasÂ  80.17, while in the group taught by conventional learning was 68,66. So it can be concluded that Model Type NHT Assisted Audio Visual Media influence on the mastery of knowledge competence of science class IV elementary school Gugus Yos Sudarso District South Denpasar Lesson 2016/2017.